2020
DOI: 10.3233/jbr-190435
|View full text |Cite
|
Sign up to set email alerts
|

Antispasmodic effects of black chokeberry (Aronia melanocarpa (Michx.) Elliott) extracts and juice and their potential use in gastrointestinal disorders

Abstract: BACKGROUND: Phytotherapy has an important role in the functional gastrointestinal and motility disorder prevention and treatment. OBJECTIVE:The aims of our study were to analyze the chemical composition and the antispasmodic activity of the dry black chokeberry ethanolic extract, waste extract and the juice in the isolated rat ileum. METHODS: The anthocyanins and flavonoids quantification was carried out by the spectrophotometric method using the HPLC instrument. The study examined the influence of the chokebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The result of the spasmolytic effect of each extract concentration was expressed as a percentage in relation to the initial spontaneous activity of the isolated ileum (% of inhibition of ileal contractility). Papaverine was used as a positive control with the concentrations of 0.01–3 μg/mL [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result of the spasmolytic effect of each extract concentration was expressed as a percentage in relation to the initial spontaneous activity of the isolated ileum (% of inhibition of ileal contractility). Papaverine was used as a positive control with the concentrations of 0.01–3 μg/mL [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The relaxations of the ileum smooth muscles, pre-contracted with potassium ions, were expressed as the percentage of the control response mediated by potassium ions. The same procedure was carried out with a calcium channel antagonist, verapamil, with the concentrations range of 0.015–1.5 μg/mL [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total polyphenol contents of chokeberry range from 1.1 g to 3.0 g gallic acid equivalents per 100 g FW (Folin-Ciocalteu assay), and the total anthocyanin contents are between 249 mg and 737 mg/100 g FW (cyanidin-3-Ogalactoside equivalent) and 9.06 ± 5.06 mg cyanidin-3-O-galactoside equivalents per g DW by liquid chromatography [48][49][50]. Six pure anthocyanin mixtures were used as the standards, and the HPLC results showed that the total anthocyanin content of chokeberries is 1480 mg/100 g FW [51].…”
Section: Chokeberrymentioning
confidence: 99%
“…Chokeberry [6,7], blackcurrant [8,9], raspberry [10,11], and strawberry [12,13] represent fruits with a high content of polyphenolic compounds. Their immunity-strengthening, 2 of 12 anti-inflammatory, and antioxidant properties have previously been reported [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%